2019
DOI: 10.1001/jama.2019.4149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trans-Nasal Evaporative Intra-arrest Cooling on Functional Neurologic Outcome in Out-of-Hospital Cardiac Arrest

Abstract: IMPORTANCE Therapeutic hypothermia may increase survival with good neurologic outcome after cardiac arrest. Trans-nasal evaporative cooling is a method used to induce cooling, primarily of the brain, during cardiopulmonary resuscitation (ie, intra-arrest). OBJECTIVE To determine whether prehospital trans-nasal evaporative intra-arrest cooling improves survival with good neurologic outcome compared with cooling initiated after hospital arrival. DESIGN, SETTING, AND PARTICIPANTS The PRINCESS trial was an investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 24 publications
(50 reference statements)
3
124
1
3
Order By: Relevance
“…Similar results were obtained when cold fluids were administered during CPR (intra-arrest TTM), which theoretically should have even greater beneficial effects on the anoxic brain [18,19]. However, the use of intraarrest TTM using a trans-nasal device, which is a method able to primarily induce brain cooling during CPR, showed some potential benefits, in particular in OHCA victims with an initial shockable rhythm [20,21], suggesting that the method used to induce intra-arrest TTM may be determinant in maximizing brain protection and avoiding adverse effects.…”
Section: Timing Of Initiationmentioning
confidence: 68%
“…Similar results were obtained when cold fluids were administered during CPR (intra-arrest TTM), which theoretically should have even greater beneficial effects on the anoxic brain [18,19]. However, the use of intraarrest TTM using a trans-nasal device, which is a method able to primarily induce brain cooling during CPR, showed some potential benefits, in particular in OHCA victims with an initial shockable rhythm [20,21], suggesting that the method used to induce intra-arrest TTM may be determinant in maximizing brain protection and avoiding adverse effects.…”
Section: Timing Of Initiationmentioning
confidence: 68%
“…The concept of achieving rapid prehospital cooling using an intranasal device that delivers a mixture of oxygen and a liquid coolant to the nasopharynx was investigated in the PRINCESS trial in patients with bystander witnessed OHCA. [44]. Although the median time to reach a target temperature less than 34°C was shorter with transnasal cooling device, survival with a favorable neurologic outcome did not differ significantly between groups (16.6% vs. 13.5%; P = 0.25).…”
Section: Timing Of Cooling Initiationmentioning
confidence: 79%
“…One of the differences between low-and high performing centres were the handling of targeted temperature management (TTM), including time to start of TTM. Interestingly, however, in the PRINCESS trial, an earlier start of TTM with early pre-hospital trans-nasal evaporative cooling did not result in improved neurological outcome after OHCA compared with cooling after hospital arrival [15]. TTM may, though, gain renewed popularity following the results of the HYPERION trial which suggested improved neurological outcome with moderate therapeutic hypothermia (33 °C) compared with targeted normothermia (37 °C) in comatose patients after cardiac arrest with non-shockable rhythm [16].…”
mentioning
confidence: 87%